Photon echoes from (In,Ga)As quantum dots embedded in a Tamm-plasmon microcavity - Salewski, M.; Poltavtsev, S. V.; Kapitonov, Yu. V.; Vondran, J.; Yakovlev, D. R.; Schneider, C.; Kamp, M.; Höfling, S.; Oulton, R.; Akimov, I. A.; Kavokin, A. V.; Bayer, M. (Physical Review B)
We report on the coherent optical response from an ensemble of (In,Ga)As quantum dots (QDs) embedded in a planar Tamm-plasmon microcavity with a quality factor of approximately 100. Significant enhancement of the light-matter interaction is demonstrated under selective laser excitation of those quantum dots which are in resonance with the cavity mode. The enhancement is manifested through Rabi oscillations of the photon echo, demonstrating coherent control of excitons with picosecond pulses at intensity levels more than an order of magnitude smaller as compared with bare quantum dots. The decay of the photon echo transients is weakly changed by the resonator, indicating a small decrease of the coherence time T2 which we attribute to the interaction with the electron plasma in the metal layer located close (40 nm) to the QD layer. Simultaneously we see a reduction of the population lifetime T1, inferred from the stimulated photon echo, due to an enhancement of the spontaneous emission by a factor of 2, which is attributed to the Purcell effect, while nonradiative processes are negligible, as confirmed from time-resolved photoluminescence.

The Role of Electronic and Phononic Excitation in the Optical Response of Monolayer WS2 after Ultrafast Excitation - Ruppert, Claudia; Chernikov, Alexey; Hill, Heather M.; Rigosi, Albert F.; Heinz, Tony F. (Nano Letters)
Transient changes of the optical response of WS2 monolayers are studied by femtosecond broadband pump–probe spectroscopy. Time-dependent absorption spectra are analyzed by tracking the line width broadening, bleaching, and energy shift of the main exciton resonance as a function of time delay after the excitation. Two main sources for the pump-induced changes of the optical response are identified. Specifically, we find an interplay between modifications induced by many-body interactions from photoexcited carriers and by the subsequent transfer of the excitation to the phonon system followed by cooling of the material through the heat transfer to the substrate.
Keywords: Atomically thin 2D materials; carrier and phonon dynamics; ultrafast spectroscopy

Tunable femtosecond near-IR source by pumping an OPA directly with a 90 MHz Yb:fiber source - Mundry, J.; Lohrenz, J.; Betz, M. (Applied Optics)
Up to 400 mW of near-IR (1370-1500 nm) femtosecond pulses are generated from an optical parametric amplifier directly driven by a Yb:fiber oscillator delivering 100 fs pulses at 1036 nm. The process is seeded by a stable supercontinuum obtained from a photonic crystal fiber. We use a single pass through a 3 mm, magnesium oxide-doped, periodically poled LiNbO3 downconversion crystal to produce a near-IR pulse train with a remarkable power stability of 1.4 % (RMS) during one hour. Tuning is achieved by the temperature and the poling period of the nonlinear crystal.
Keywords: Infrared and far-infrared lasers; Ultrafast lasers; Nonlinear optics; parametric processes; Parametric oscillators and amplifiers; Femtosecond pulses; Fiber lasers; Fused silica; Laser systems; Photonic crystal fibers; Pulse propagation

Picosecond Control of Quantum Dot Laser Emission by Coherent Phonons - Czerniuk, T.; Wigger, D.; Akimov, A. V.; Schneider, C.; Kamp, M.; Höfling, S.; Yakovlev, D. R.; Kuhn, T.; Reiter, D. E.; Bayer, M. (Physical Review Letters)
A picosecond acoustic pulse can be used to control the lasing emission from semiconductor nanostructures by shifting their electronic transitions. When the active medium, here an ensemble of (In,Ga)As quantum dots, is shifted into or out of resonance with the cavity mode, a large enhancement or suppression of the lasing emission can dynamically be achieved. Most interesting, even in the case when gain medium and cavity mode are in resonance, we observe an enhancement of the lasing due to shaking by coherent phonons. In order to understand the interactions of the nonlinearly coupled photon-exciton-phonon subsystems, we develop a semiclassical model and find an excellent agreement between theory and experiment.

Acousto-optical nanoscopy of buried photonic nanostructures - Czerniuk, T.; Schneider, C.; Kamp, M.; Höfling, S.; Glavin, B. A.; Yakovlev, D. R.; Akimov, A. V.; Bayer, M. (Optica)
We develop a nanoscopy method with in-depth resolution for layered photonic devices. Photonics often requires tailored light field distributions for the optical modes used, and an exact knowledge of the geometry of a device is crucial to assess its performance. The presented acousto-optical nanoscopy method is based on the uniqueness of the light field distributions in photonic devices: for a given wavelength, we record the reflectivity modulation during the transit of a picosecond acoustic pulse. The temporal profile obtained can be linked to the internal light field distribution. From this information, a reverse-engineering procedure allows us to reconstruct the light field and the underlying photonic structure very precisely. We apply this method to the slow light mode of an AlAs/GaAs micropillar resonator and show its validity for the tailored experimental conditions.

Double resonant plasmonic nanoantennas for efficient second harmonic generation in zinc oxide - Weber, Nils; Protte, Maximilian; Walter, Felicitas; Georgi, Philip; Zentgraf, Thomas; Meier, Cedrik (Physical Review B)

Ultrathin Nonlinear Metasurface for Optical Image Encoding - Walter, Felicitas; Li, Guixin; Meier, Cedrik; Zhang, Shuang; Zentgraf, Thomas (Nano Letters)

Damping of Rabi oscillations in intensity-dependent photon echoes from exciton complexes in a CdTe/(Cd,Mg)Te single quantum well - Poltavtsev, S. V.; Reichelt, Matthias; Akimov, I. A.; Karczewski, G.; Wiater, M.; Wojtowicz, T.; Yakovlev, D. R.; Meier, Torsten; Bayer, M. (Physical Review B)

Polarization-entangled twin photons from two-photon quantum-dot emission - Heinze, Dirk; Zrenner, Artur; Schumacher, Stefan (Physical Review B)
Semiconductor quantum dots are promising sources for polarization-entangled photons. As an alternative to the usual cascaded biexciton-exciton emission, direct two-photon emission from the biexciton can be used. With a high-quality optical resonator tuned to half the biexciton energy, a large proportion of the photons can be steered into the two-photon emission channel. In this case the degree of polarization entanglement is inherently insensitive to the exciton fine-structure splitting. In the present work we analyze the biexciton emission with particular emphasis on the influence of coupling of the quantum-dot cavity system to its environment. Especially for a high-quality cavity, the coupling to the surrounding semiconductormaterial can open up additional phonon-assisted decay channels. Our analysis demonstrates that with the cavity tuned to half the biexciton energy, the potentially detrimental influence of the phonons on the polarization entanglement is strongly suppressed—high degrees of entanglement can still be achieved. We further discuss spectral properties and statistics of the emitted twin photons.

High-Resolution Two-Dimensional Optical Spectroscopy of Electron Spins - Salewski, M.; Poltavtsev, S. V.; Yugova, I. A.; Karczewski, G.; Wiater, M.; Wojtowicz, T.; Yakovlev, D. R.; Akimov, I. A.; Meier, Torsten; Bayer, M. (Physical Review X)

Nonlinear photonic metasurfaces - Li, Guixin; Zhang, Shuang; Zentgraf, Thomas (Nature Reviews Materials)

Fabrication of fully undercut ZnO-based photonic crystal membranes with 3D optical confinement - Hoffmann, Sandro Phil; Albert, Maximilian; Meier, Cedrik (Superlattices and Microstructures)

Ultrafast dynamical response of the lower exciton-polariton branch in CdZnTe - Lohrenz, J.; Melzer, S.; Ruppert, C.; Akimov, I. A.; Mariette, H.; Reichelt, Matthias; Trautmann, Alexander; Meier, Torsten; Betz, M. (Physical Review B)
We investigate the transient optical response in high-quality Cd0.88Zn0.12Te crystals in the regime of slow light propagation on the lower exciton-polariton branch. Femtosecond photoexcitation leads to very substantial transmission changes in a ∼10-meV broad spectral range within the transparency window of the unexcited semiconductor. These nonlinear optical signatures decay on picosecond time scales governed by carrier thermalization and recombination. The temporal and spectral dependence indicate the dynamical optical response as arising from excitation-induced dephasing and perturbed free induction decay. Model simulations for the optical response taking into account the actual exciton-polariton dispersion and excitation-induced dephasing of a nonlinearly driven two-level system support this interpretation.

Two-dimensional symbiotic solitons and vortices in binary condensates with attractive cross-species interaction - Ma, Xuekai; Driben, Rodislav; Malomed, Boris A.; Meier, Torsten; Schumacher, Stefan (Scientific Reports)

All-optical tailoring of single-photon spectra in a quantum-dot microcavity system - Breddermann, D.; Heinze, D.; Binder, R.; Zrenner, Artur; Schumacher, Stefan (Physical Review B)
Semiconductor quantum-dot cavity systems are promising sources for solid-state-based on-demand generation of single photons for quantum communication. Commonly, the spectral characteristics of the emitted single photon are fixed by system properties such as electronic transition energies and spectral properties of the cavity. In the present work we study cavity-enhanced single-photon generation from the quantum-dot biexciton through a partly stimulated nondegenerate two-photon emission. We show that frequency and linewidth of the single photon can be fully controlled by the stimulating laser pulse, ultimately allowing for efficient all-optical spectral shaping of the single photon.

Simulations of high harmonic generation from plasmonic nanoparticles in the terahertz region - Grynko, Yevgen; Zentgraf, Thomas; Meier, Torsten; Förstner, Jens (Applied Physics B)
Keywords: tet_topic_meta; tet_topic_shg

Spin and wavelength multiplexed nonlinear metasurface holography - Ye, Weimin; Zeuner, Franziska; Li, Xin; Reineke, Bernhard; He, Shan; Qiu, Cheng-Wei; Liu, Juan; Wang, Yongtian; Zhang, Shuang; Zentgraf, Thomas (Nature Communications)

Giant Nonlinear Optical Activity of Achiral Origin in Planar Metasurfaces with Quadratic and Cubic Nonlinearities - Chen, Shumei; Zeuner, Franziska; Weismann, Martin; Reineke, Bernhard; Li, Guixin; Valev, Ventsislav Kolev; Cheah, Kok Wai; Panoiu, Nicolae Coriolan; Zentgraf, Thomas; Zhang, Shuang (Advanced Materials)

Rotational Doppler effect in nonlinear optics - Li, Guixin; Zentgraf, Thomas; Zhang, Shuang (Nature Physics)

Designermaterialien für nichtlineare Optik - Probst, Heike; Zentgraf, Thomas (Physik in unserer Zeit)